Role of Transient Elastography (Fibroscan) in Differentiating Severe Acute Hepatitis and Acute on Chronic Liver Failure() - Sharma, Praveen (J Clin Exp Hepatol, 2015)
INTRODUCTION: It is difficult to differentiate acute severe hepatitis (AH) with acute on chronic liver failure (ACLF). Aim was to study the role of transient elastography (Fibroscan) in identifying the patients with AH and ACLF. MATERIALS AND METHODS: Consecutive patients of severe AH or ACLF presented within two weeks of jaundice were enrolled. LSM and liver function tests were done at admission, week 1, 4 and at 6 months. Diagnosis of ACLF was based on documenting cirrhotic morphology on imaging and/or liver biopsy and follow-up of these patients for six months. Similarly, AH patients were diagnosed based on serology, no features of cirrhosis on imaging and follow-up of these patients for 6 months documenting reversal of liver stiffness measurement (LSM) to normal. RESULTS: 104 patients were included in the final analysis (AH, n = 59, ACLF, n = 45). Out of 59 patients in severe AH group, etiology of acute hepatitis included hepatitis A (HAV, n = 22), hepatitis E (HEV, n = 21), hepatitis B (HBV, n = 4), indeterminate (n = 8) and drug induced liver injury (n = 4). Similarly for ACLF, the causes of chronic liver disease were alcohol (n = 26), hepatitis B (n = 7), hepatitis C (n = 2) and cryptogenic (n = 10). Patients with ACLF were significantly older, had low hemoglobin, low albumin, high bilirubin and lower transaminases level compared to severe AH at admission. LSM was higher in patients with ACLF compared to severe AH (61 ± 18 kPa vs 15 ± 6.4 kPa, P = 0.001) at admission. On multivariate analysis of noninvasive tests only LSM was found to differentiate AH with ACLF significantly. When we took a cutoff of 26 kPa the sensitivity and specificity of diagnosis of ACLF were 96% and 93%, respectively, with area under the curve was 0.98 (0.95–1.005), P = 0.001. CONCLUSION: LSM could differentiate patients with severe AH and ACLF at admission.